Thematic evolution of pregnancy stress research: A SciMAT-based bibliometric review - Nurul Jannah; Sri Lestari; Lisnawati Ruhaena (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Research on pregnancy-related stress has expanded markedly alongside growing recognition of maternal mental health as a key determinant of perinatal outcomes. Evidence shows that stress during pregnancy can lead to lasting physiological and psychological consequences for both mothers and offspring. However, a comprehensive understanding of thematic development and research trajectories in this field remains limited. Purpose: To map the principal thematic domains in pregnancy-related stress research and examine the evolution of research topics, dominant scientific orientations, and methodological trends over time. Method: A bibliometric analysis was conducted on 365 Scopus-indexed articles using SciMAT. Four analytical approaches were applied: performance analysis, keyword evolution analysis, longitudinal analysis, and period-based thematic analysis. The study period (1997–2025) was divided into five intervals to capture temporal dynamics and shifts in thematic networks. Results: Core themes such as risk factors, prenatal exposure delayed effects, and anxiety disorders demonstrated high centrality and density, indicating their foundational role. Emerging themes including paternal care, circadian rhythms, and non-pharmacological therapies reflect a growing multidisciplinary and holistic orientation. Persistent gaps were identified, particularly limited validation of peripartum anxiety measures, underuse of biometric methods, and insufficient attention to culturally responsive interventions. Conclusion: This study maps pregnancy-related stress across five periods, highlighting persistent links to risk factors, prenatal exposure, and long-term outcomes. Core themes include delayed effects and anxiety disorders, with emerging focus on paternal roles, biological rhythms, and sex differences. Findings call for rigorous, longitudinal, cross-cultural research using digital tools and SciMAT insights.